Management Model of BUMDes Girimulyo in the Era of Digitalization of Giripurno Village Community, Batu City - Mohammad Izza Nur Rahman; Sulismadi (Indonesian Academy of Social and Religious Research (IASRR), 2025)
This study explores the management model of the Girimulyo Village-Owned Enterprise (BUMDes) in Giripurno Village, Batu City, within the context of village digitalization. The Girimulyo BUMDes oversees key businesses, including an egg-laying chicken farm and cafes, which contribute to local economic empowerment. Despite its considerable potential, the management of BUMDes still relies on traditional practices that do not fully leverage digital technology, leading to suboptimal effectiveness and limited capacity for community empowerment. Employing a descriptive qualitative approach, this research utilizes case studies, purposive sampling, observation, interviews, and documentation to gather data. The findings suggest that the integration of digital technology into BUMDes operations could enhance administrative efficiency, transparency, and accountability, while also broadening marketing reach. Furthermore, the quality of human resources is identified as a crucial factor in the success of digitalization efforts. However, challenges such as inadequate infrastructure, resistance to change, and the need for training must be addressed to ensure the sustainability of digitalization. The study concludes that a management model supported by digital innovation and human resource development can foster the independence and well-being of village communities in an inclusive and sustainable manner.